2021
DOI: 10.3390/ijerph18073667
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Changes during the COVID-19 Pandemic for Caregivers of Children with ADHD and/or ASD

Abstract: The COVID-19 pandemic has presented many challenges to caregivers of children. Families with children with attention-deficit/hyperactivity disorder (ADHD) and/or autism spectrum disorder (ASD) are an understudied but potentially vulnerable population to changes during the outbreak. As such, the aim of this study was to contrast quality of life for caregivers of children with ADHD and/or ASD, before and during the pandemic, compared to caregivers of neurotypical (NT) children. Total, Parent Health-Related Quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
49
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 80 publications
4
49
1
4
Order By: Relevance
“…15 , 30 , 31 Recent studies recorded a declined social support, 3 and quality of life for caregivers during the pandemic, issues that increase their social burden. 16 Similar to our results, about 78% of the participants indicated that their relationships with other family members, relatives, friends, and acquaintances were suffering because of the care. In terms of the communication aspect, the current study showed that (74.7%) of children can communicate well with their caregivers during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…15 , 30 , 31 Recent studies recorded a declined social support, 3 and quality of life for caregivers during the pandemic, issues that increase their social burden. 16 Similar to our results, about 78% of the participants indicated that their relationships with other family members, relatives, friends, and acquaintances were suffering because of the care. In terms of the communication aspect, the current study showed that (74.7%) of children can communicate well with their caregivers during the COVID-19 pandemic.…”
Section: Discussionsupporting
confidence: 89%
“…15 Recent studies recorded a declined social support 3 and quality of life for caregivers during the pandemic, issues that increase their social burden. 16 …”
Section: Introductionmentioning
confidence: 99%
“…As raising children with disabilities is stressful under routine conditions, the additional responsibilities of remote learning, including creating structure and organization, coordinating with teachers and school personnel, home and work demands, and supporting children’s emotions and behaviors, contributed to significant additional burden for these families [ 63 , 66 •, 67 •, 68 ••, 73 , 78 – 89 ]. Studies have shown that stress is buffered by social support [ 90 , 91 ] (including professional support, respite, assistance from family or friends), and as a result of the social distancing and isolation measures implemented during pandemic, many families of children with disabilities experienced heightened stress with minimal aid [ 68 ••, 81 , 83 , 84 , 86 , 87 , 92 – 96 ].…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
“…Parental stress was reported to be related to protracted closure of schools and lack of access to child’s therapies, remote learning, stay-at-home orders, concern of infection with COVID-19, loss of family and friends due to COVID-19, working remotely while caring for children, limited job flexibility, economic hardship, lack of social support, their own mental well-being, and managing worsening of their children’s behaviors and sleep among many other stressors [ 63 , 66 •, 67 •, 68 ••, 73 , 78 – 84 , 86 , 87 , 89 , 120 ]. In addition to elevated levels of stress, parents of children with disabilities endorsed significantly higher levels of mental health symptoms overall during the COVID-19 pandemic, with some studies correlating elevated stress scores and poor mental health outcomes [ 81 , 83 , 84 , 86 , 92 – 95 ].…”
Section: Covid-19 Pandemicmentioning
confidence: 99%
“…The COVID-19 pandemic not only disrupted the lifestyles and daily routines and deteriorated the behavioral problems in children with NDDs, but also obstructed the social and medical support for caregivers [ 13 ]. Caregivers of children with ADHD or ASD reported higher levels of burden, depression, anxiety, and stress [ 14 ] and a greater decrease in their quality of life compared with caregivers of children with normal development during the pandemic [ 15 ].…”
Section: Introductionmentioning
confidence: 99%